A citation network analysis of career mentoring across disciplines: A roadmap for mentoring research in sport. (July 2020) - Lefebvre, Jordan S.; Bloom, Gordon A.; Loughead, Todd M.
Abstract: Objective: Given our limited understanding of mentoring in sport, reviewing research from other disciplines has the potential to advance knowledge in this context. Therefore, the purpose of this study was to synthesize and evaluate the mentoring literature across disciplines in order to bridge existing knowledge and to situate the mentoring in sport literature. Design: A citation network analysis. Method: A comprehensive literature search was conducted to locate influential career mentoring articles, books, and book chapters across all disciplines. Subsequently, this body of literature was evaluated using citation network to (a) identify the major career mentoring disciplines, (b) locate the most influential career mentoring texts, (c) evaluate the transfer of knowledge across disciplines, and (d) situate and evaluate the mentoring in sport literature. Results: The literature search resulted in a mentoring network of 1, 819 texts and 10, 951 citation links. Five major mentoring disciplines emerged: academic medicine, industrial and organizational psychology, education, nursing, and psychology. The industrial and organizational psychology and academic medicine disciplines were the most substantial mentoring disciplines. Further, the findings suggest the literature is relatively disconnected within and across disciplines. In regard to sport, the mentoring research represented 1.47% of the full-network (29 texts and 50 citation relations) and is interwoven into the industrial and organizational psychology literature. Conclusion: Given the limited sport texts uncovered in the citation network analysis, sport scholars can stand to benefit from the wealth of existing career mentoring literature in other disciplines. Accordingly, the identification of seminal career mentoring disciplines and texts serves to provide sport mentoring scholars with a roadmap to further promote the advancement and dissemination of mentoring knowledge and research. Highlights: The career mentoring literature is largely comprised of five major mentoring disciplines. Academic medicine and industrial/organizational psychology are the most substantial career mentoring disciplines. There is an interdisciplinary disconnect; mentoring disciplines are working in silos. Sport mentoring is interconnected with the industrial/organizational psychology literature. Sport scholars can learn from other career mentoring disciplines (e.g., education and psychology).